Light-adjusting sheet and method for manufacturing the same
Patent Information
- Application Number
- JP2022003782
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-01-13
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2041-03-24
AI Technical Summary
【0013】 本発明によれば、電位差の変化に応答して光透過率を変化させることに要する時間を短縮可能にした調光シート、および調光シートの製造方法を提供できる。
Smart Images

Figure 0007609082000010 
Figure 0007609082000011 
Figure 0007609082000012
Abstract
Description
[Technical field]
[0001] The present invention relates to a light controlling sheet containing a non-polymerizable liquid crystal compound, and a method for producing the light controlling sheet. [Background technology]
[0002] The light-controlling sheet includes a first transparent electrode layer, a second transparent electrode layer, and a light-controlling layer sandwiched between the first transparent electrode layer and the second transparent electrode layer. The orientation state of the non-polymerizable liquid crystal compound contained in the light-controlling layer changes the light transmittance of the light-controlling sheet in response to a change in the potential difference between the two transparent electrode layers. For example, when the orientation order of the non-polymerizable liquid crystal compound is established, the light-controlling sheet exhibits high light transmittance. When the long axis direction of the non-polymerizable liquid crystal compound is disordered, the light-controlling sheet exhibits low light transmittance (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2018-45135 A Summary of the Invention [Problem to be solved by the invention]
[0004] Meanwhile, the responsiveness of the light transmittance to a change in the potential difference between the two transparent electrode layers changes based on the environmental temperature in which the light-controlling sheet is installed. The wider the range of environmental temperatures in which the light transmittance changes within a specified time from switching the potential difference, the wider the fields of application of the light-controlling sheet. In particular, for application fields requiring operation in cold regions, it is required that the light transmittance changes within a specified time at low environmental temperatures. For example, when a light-controlling sheet is attached to the window glass of a vehicle, the environmental temperature in which the light-controlling sheet is installed drops significantly more than that of the items in the vehicle cabin. If the time required to change the light transmittance can be shortened in a low-temperature environment, the suitability of the light-controlling sheet for use in vehicles will be improved. [Means for solving the problem]
[0005] The light-adjusting sheet for solving the above-mentioned problems includes an organic polymer layer that defines a plurality of voids, and a liquid crystal composition that contains a non-polymerizable liquid crystal compound and fills the voids, and the light-adjusting sheet changes the transmittance of visible light by driving the non-polymerizable liquid crystal compound, the weight ratio of the organic polymer layer to the total weight of the organic polymer layer and the liquid crystal composition is 30% by mass or more and 60% by mass or less, the liquid crystal composition contains a non-polymerizable viscosity reducing agent, and all of the non-polymerizable viscosity reducing agents contained in the liquid crystal composition satisfy the following formula (1), and the weight ratio of all of the non-polymerizable viscosity reducing agents contained in the liquid crystal composition to the total weight of the non-polymerizable liquid crystal compound and the non-polymerizable viscosity reducing agents is 2% by mass or more and 6% by mass or less. In formula (1), X is a linear or branched alkyl group or an aryl group having 1 to 6 carbon atoms, and R 1 , R 2 , R 3 are each independently a hydrogen atom or a functional group represented by formula (2) bonded to one or each of the carbons constituting X, and r 4 is a linear or branched alkyl group or an ether group having 1 to 10 carbon atoms. 5 is a straight-chain or branched alkyl group or an ether group having from 1 to 10 carbon atoms.
[0006] [ka]
[0007] [ka]
[0008] A method for manufacturing a light-controlling sheet for solving the above problems includes an organic polymer layer that defines a plurality of voids, and a liquid crystal composition that contains a non-polymerizable liquid crystal compound and fills the voids, and the method changes the transmittance of visible light by driving the non-polymerizable liquid crystal compound, and includes phase-separating liquid crystal particles made of the liquid crystal composition from the organic polymer layer by polymerizing the ultraviolet-curable compound in a layer containing the liquid crystal composition and the ultraviolet-curable compound, wherein the weight ratio of the organic polymer layer to the total weight of the organic polymer layer and the liquid crystal composition is 30% by mass or more and 60% by mass or less, the liquid crystal composition contains a non-polymerizable viscosity reducing agent, and all of the non-polymerizable viscosity reducing agents contained in the liquid crystal composition satisfy the above formula (1), and the weight ratio of all of the non-polymerizable viscosity reducing agents contained in the liquid crystal composition to the total weight of the non-polymerizable liquid crystal compound and the non-polymerizable viscosity reducing agents is 2% by mass or more and 6% by mass or less.
[0009] According to each of the above configurations, the localization of electrons in the non-polymerizable liquid crystal compound and the localization of electrons in the non-polymerizable viscosity reducing agent interact with each other, making it easier for the alkyl groups at the ends of the non-polymerizable viscosity reducing agent to be interposed between adjacent non-polymerizable liquid crystal compounds. The presence of the alkyl groups, which are non-polar groups, between the non-polymerizable liquid crystal compounds weakens the intermolecular interactions in the non-polymerizable liquid crystal compounds. This makes it possible to increase the responsiveness of the light transmittance at low environmental temperatures such as -20°C.
[0010] In addition, the configuration in which the liquid crystal composition fills the gaps partitioned by the organic polymer layer is formed by using a photopolymerizable compound and a liquid crystal composition to form the organic polymer layer, and phase-separating the liquid crystal composition from the organic polymer layer through polymerization of the photopolymerizable compound. In this case, the non-polymerizable viscosity reducer is suitable for phase-separation from the organic polymer layer. Furthermore, the low molecular weight structure represented by the above formulas (1) and (2) is also suitable for diffusing from the polymer of the photopolymerizable compound, i.e., for phase-separation from the organic polymer layer.
[0011] In the above light-adjusting sheet, X in the formula (1) is a linear alkyl group having 1 to 6 carbon atoms, and R 1 is a functional group represented by the formula (2), and in the formula (1), R 2 , R 3 may each independently be a hydrogen atom.
[0012] In the above light controlling sheet, the NI point of the non-polymerizable liquid crystal compound may be 100° C. or higher and 145° C. or lower. Effect of the Invention
[0013] According to the present invention, it is possible to provide a light controlling sheet that makes it possible to shorten the time required to change the light transmittance in response to a change in potential difference, and a method for manufacturing the light controlling sheet. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a diagram showing a schematic configuration of a light control device according to an embodiment. [Diagram 2] FIG. 2 is a diagram showing a cross-sectional configuration of a light adjusting sheet according to an embodiment. [Diagram 3] 1 is a table showing the composition and evaluation results of polymer-dispersed liquid crystal compositions of each example. [Figure 4] 1 is a table showing the composition and evaluation results of polymer-dispersed liquid crystal compositions of each example. [Diagram 5] 1 is a table showing the composition and evaluation results of polymer-dispersed liquid crystal compositions of each example. [Figure 6] 1 is a table showing the composition and evaluation results of polymer-dispersed liquid crystal compositions of each example. [Figure 7] 1 is a table showing the composition and evaluation results of polymer-dispersed liquid crystal compositions of respective comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] An embodiment of a light control sheet, a polymer-dispersed liquid crystal composition, and a method for manufacturing the light control sheet will be described. First, the configuration of the light control device will be described with reference to Fig. 1. Next, the configuration of the light control sheet and the polymer-dispersed liquid crystal composition will be described with reference to Fig. 2. Finally, the method for manufacturing the light control sheet and each example of the light control sheet will be described.
[0016] The light-controlling sheet is attached to a transparent substrate. The transparent substrate is a glass body or a resin body. Examples of the transparent substrate are window glass installed in a moving body such as a vehicle or an aircraft, window glass installed in a building, and a partition installed in a vehicle or indoors. The surface to which the light-controlling sheet is attached is flat or curved. The light-controlling sheet may be sandwiched between two transparent substrates.
[0017] The driving type of the light-controlling sheet is either normal type or reverse type. A normal type light-controlling sheet transitions from an opaque state to a transparent state when a voltage is applied, and returns from the transparent state to the opaque state when the voltage application is removed. A reverse type light-controlling sheet transitions from a transparent state to an opaque state when a voltage is applied, and returns from the opaque state to the transparent state when the voltage application is removed.
[0018] The normal type and reverse type have in common the fact that they are equipped with two transparent electrode layers and a light control layer. Below, the configuration and action of the reverse type will be mainly explained, and the configuration of the normal type that differs from the reverse type will be noted, while the configuration of the normal type that overlaps with the reverse type will be omitted.
[0019] [Light control device] 1, the light control device 10 includes a light control sheet 11 and a driving unit 12. The light control sheet 11 includes a light control layer 31, a first alignment layer 32, a second alignment layer 33, a first transparent electrode layer 34, a second transparent electrode layer 35, a first transparent support layer 36, and a second transparent support layer 37.
[0020] The light control layer 31 is located between the first alignment layer 32 and the second alignment layer 33. A first surface 31F of the light control layer 31 contacts the first alignment layer 32, and a second surface 31S of the light control layer 31 contacts the second alignment layer 33. The first alignment layer 32 is located between the light control layer 31 and the first transparent electrode layer 34, and contacts both the light control layer 31 and the first transparent electrode layer 34. The second alignment layer 33 is located between the light control layer 31 and the second transparent electrode layer 35, and contacts both the light control layer 31 and the second transparent electrode layer 35.
[0021] The first transparent electrode layer 34 is connected to the driving unit 12 through the first connection terminal 22A and the first wiring 23A. The first transparent electrode layer 34 is located between the first alignment layer 32 and the first transparent support layer 36, and contacts the first alignment layer 32 and the first transparent support layer 36. The second transparent electrode layer 35 is connected to the driving unit 12 through the second connection terminal 22B and the second wiring 23B. The second transparent electrode layer 35 is located between the second alignment layer 33 and the second transparent support layer 37, and contacts the second alignment layer 33 and the second transparent support layer 37.
[0022] The light control layer 31 includes an organic polymer layer 31P (see FIG. 2) and a liquid crystal composition 31LC (see FIG. 2). The organic polymer layer 31P defines voids 31D filled with the liquid crystal composition 31LC. The type of retention of the liquid crystal composition 31LC by the organic polymer layer 31P is any one selected from the group consisting of a polymer dispersion type, a polymer network type, and a capsule type.
[0023] The polymer dispersion type light control layer 31 has an organic polymer layer 31P that partitions a large number of isolated voids 31D, and holds a liquid crystal composition 31LC in the voids 31D dispersed in the organic polymer layer 31P. The polymer network type light control layer 31 has an organic polymer layer 31P that defines three-dimensional mesh-like voids 31D, and holds a liquid crystal composition 31LC in the interconnected mesh-like voids 31D. The capsule type light control layer 31 holds a liquid crystal composition 31LC in capsule-like voids 31D dispersed in the organic polymer layer 31P.
[0024] The first alignment layer 32 and the second alignment layer 33 each regulate the alignment direction of the non-polymerizable liquid crystal compound LCM. The first alignment layer 32 and the second alignment layer 33 each appear colorless and transparent or colored and transparent. The first alignment layer 32 and the second alignment layer 33 are vertical alignment films. The vertical alignment film aligns the major axis direction of the non-polymerizable liquid crystal compound LCM with the thickness direction of the light control layer 31, and allows visible light to pass through the light control layer 31.
[0025] The material constituting the first alignment layer 32 and the second alignment layer 33 is an organic polymer compound or an inorganic oxide. The organic polymer compound is any one selected from the group consisting of polyimide, polyamide, polyvinyl alcohol, and cyanide compounds. The inorganic oxide is any one selected from the group consisting of silicon oxide, zirconium oxide, and silicone.
[0026] The first transparent electrode layer 34 and the second transparent electrode layer 35 are visually recognized as colorless and transparent or colored and transparent, respectively. The materials constituting the first transparent electrode layer 34 and the second transparent electrode layer 35 are conductive inorganic oxides, metals, or conductive organic polymer compounds, respectively. An example of the conductive inorganic oxide is any one selected from the group consisting of indium tin oxide, fluorine-doped tin oxide, tin oxide, and zinc oxide. The metal is gold or silver nanowires. An example of the conductive organic polymer compound is any one selected from the group consisting of carbon nanotubes and poly(3,4-ethylenedioxythiophene).
[0027] The first transparent support layer 36 and the second transparent support layer 37 are visually recognized as colorless and transparent or colored and transparent, respectively. The materials constituting the first transparent support layer 36 and the second transparent support layer 37 are organic polymer compounds or inorganic polymer compounds, respectively. An example of the organic polymer compound is any one selected from the group consisting of polyester, polyacrylate, polycarbonate, and polyolefin. An example of the inorganic polymer compound is any one selected from the group consisting of silicon oxide, silicon oxynitride, and silicon nitride.
[0028] The driving unit 12 is connected to the first transparent electrode layer 34 and the second transparent electrode layer 35 separately. The driving unit 12 applies a driving voltage between the first transparent electrode layer 34 and the second transparent electrode layer 35. The driving voltage is a voltage for changing the alignment state of the non-polymerizable liquid crystal compound LCM. The driving unit 12 changes the alignment state of the non-polymerizable liquid crystal compound LCM to switch the light control sheet 11 from one of a transparent state and an opaque state to the other. The opaque state has a lower parallel transmittance than the transparent state and also has a higher haze than the transparent state.
[0029] When the application of the driving voltage is released, the non-polymerizable liquid crystal compound LCM receives an alignment regulation force from the first alignment layer 32 and the second alignment layer 33, and the long axis direction of the non-polymerizable liquid crystal compound LCM is aligned with the thickness direction of the light control layer 31. As a result, the light control sheet 11 suppresses scattering in the light control layer 31 over the entire visible light range and becomes transparent.
[0030] When the driving voltage starts to be applied, the non-polymerizable liquid crystal compound LCM is subjected to an orientation control force by the electric field, and the long axis direction of the non-polymerizable liquid crystal compound LCM starts to move in a direction perpendicular to the electric field direction. At this time, the long axis direction of the non-polymerizable liquid crystal compound LCM is restricted by the intermolecular interactions in the liquid crystal composition 31LC and the size of the voids 31D, and cannot move sufficiently, becoming disordered. As a result, the light control sheet 11 causes scattering in the light control layer 31 over the entire visible light range, and becomes opaque.
[0031] When the application of the driving voltage is released again, the orientation restricting force of the electric field is released from the non-polymerizable liquid crystal compound LCM, and the major axis direction of the non-polymerizable liquid crystal compound LCM is aligned with the thickness direction of the light control layer 31 according to the orientation restricting forces of the first alignment layer 32 and the second alignment layer 33. As a result, the light control sheet 11 suppresses scattering in the light control layer 31 over the entire visible light range, and becomes transparent again.
[0032] If the light-adjusting sheet 11 is configured to switch between a transparent state and an opaque state based on a change in the alignment state of the non-polymerizable liquid crystal compound LCM by application of a voltage, the first alignment layer 32 and the second alignment layer 33 may be omitted. In this case, the first surface 31F of the light-adjusting layer 31 contacts the first transparent electrode layer 34, and the second surface 31S of the light-adjusting layer 31 contacts the second transparent electrode layer 35. In other words, the driving type of the light-adjusting sheet 11 may be changed from a reverse type to a normal type.
[0033] In the case where the first alignment layer 32 and the second alignment layer 33 are omitted, when the application of the driving voltage is released, the non-polymerizable liquid crystal compound LCM is not subjected to an alignment restraining force, and the long axis direction of the non-polymerizable liquid crystal compound LCM becomes disordered. As a result, the light control sheet 11 causes scattering in the light control layer 31 over the entire visible light range, and becomes opaque.
[0034] When a driving voltage is applied, the non-polymerizable liquid crystal compound LCM is subjected to an orientation control force by the electric field, and the long axis direction of the non-polymerizable liquid crystal compound LCM is aligned along the electric field direction. As a result, the light controlling sheet 11 suppresses scattering in the light controlling layer 31 over the entire visible light range and becomes transparent.
[0035] When the application of the driving voltage is released again, the orientation restriction force of the non-polymerizable liquid crystal compound LCM due to the electric field is released, and the long axis direction of the non-polymerizable liquid crystal compound LCM becomes disordered. As a result, the light-controlling sheet 11 causes scattering in the light-controlling layer 31 over the entire visible light range, and becomes opaque again.
[0036] [Light control sheet] As shown in FIG. 2, the light control layer 31 includes an organic polymer layer 31P, a liquid crystal composition 31LC, and a spacer SP. The organic polymer layer 31P defines a void 31D filled with the liquid crystal composition 31LC. The organic polymer layer 31P defines a plurality of voids 31D. The void 31D may be isolated from other adjacent voids 31D, or may be connected to other adjacent voids 31D. The voids 31D have two or more sizes, including a relatively large void 31H1 and a relatively small void 31H2. The shape of the void 31D is spherical, ellipsoidal, or irregular.
[0037] [Photopolymerizable compound] The organic polymer layer 31P is a cured product of a photopolymerizable compound. The photopolymerizable compound may be an ultraviolet curable compound or an electron beam curable compound. The photopolymerizable compound is compatible with the liquid crystal composition 31LC. In order to improve the dimensional controllability of the gap 31D, the photopolymerizable compound is preferably an ultraviolet curable compound. An example of the ultraviolet curable compound includes a polymerizable unsaturated bond at the end of the molecular structure. Alternatively, the ultraviolet curable compound includes a polymerizable unsaturated bond other than at the end of the molecular structure. The photopolymerizable compound is one type of polymerizable compound, or a combination of two or more types of polymerizable compounds.
[0038] The ultraviolet-curable compound is at least one selected from the group consisting of acrylate compounds, methacrylate compounds, styrene compounds, thiol compounds, and oligomers of each of these compounds.
[0039] The acrylate compounds include monoacrylate compounds, diacrylate compounds, triacrylate compounds, and tetraacrylate compounds. Examples of the acrylate compounds are butyl ethyl acrylate, ethylhexyl acrylate, and cyclohexyl acrylate. Examples of the methacrylate compounds are dimethacrylate compounds, trimethacrylate compounds, and tetramethacrylate compounds. Examples of the methacrylate compounds are N,N-dimethylaminoethyl methacrylate, phenoxyethyl methacrylate, methoxyethyl methacrylate, and tetrahydrofurfuryl methacrylate. Examples of the thiol compounds are 1,3-propanedithiol and 1,6-hexanedithiol. Examples of the styrene compounds are styrene and methylstyrene.
[0040] The lower limit of the content of the organic polymer layer 31P relative to the total amount of the organic polymer layer 31P and the liquid crystal composition 31LC is 20 mass %, and more preferably 30 mass %. The upper limit of the content of the organic polymer layer 31P relative to the total amount of the organic polymer layer 31P and the liquid crystal composition 31LC is 70 mass %, and more preferably 60 mass %.
[0041] The lower limit and upper limit of the content of the organic polymer layer 31P are within a range where the liquid crystal particles of the liquid crystal composition 31LC are phase-separated from the cured product of the photopolymerizable compound during the curing process of the photopolymerizable compound. When it is necessary to increase the mechanical strength of the organic polymer layer 31P, it is preferable that the lower limit of the content of the organic polymer layer 31P is high. When it is necessary to reduce the driving voltage of the non-polymerizable liquid crystal compound LCM, it is preferable that the upper limit of the content of the organic polymer layer 31P is low.
[0042] [Liquid crystal composition] The liquid crystal composition 31LC is a polymer-dispersed liquid crystal composition. The liquid crystal composition 31LC contains a non-polymerizable liquid crystal compound LCM and a non-polymerizable viscosity reducing agent DP, and is filled in the gap 31D. The liquid crystal composition 31LC may contain a dichroic dye, an antifoaming agent, an antioxidant, a weathering agent, and a solvent. Examples of the weathering agent include an ultraviolet absorber and a light stabilizer.
[0043] [Non-polymerizable liquid crystal compound] The dielectric constant of the non-polymerizable liquid crystal compound LCM in the long axis direction is larger than the dielectric constant of the non-polymerizable liquid crystal compound LCM in the short axis direction, and has a positive dielectric anisotropy. Alternatively, the dielectric constant of the non-polymerizable liquid crystal compound LCM in the long axis direction is lower than the dielectric constant of the non-polymerizable liquid crystal compound LCM in the short axis direction, and has a negative dielectric anisotropy. The dielectric anisotropy of the non-polymerizable liquid crystal compound LCM is appropriately selected based on the presence or absence of each alignment layer in the light control sheet 11 and the driving type.
[0044] The non-polymerizable liquid crystal compound LCM is at least one selected from the group consisting of Schiff base type, azo type, azoxy type, biphenyl type, terphenyl type, benzoic acid ester type, tolan type, pyrimidine type, pyridazine type, cyclohexane carboxylate type, phenylcyclohexane type, biphenylcyclohexane type, dicyanobenzene type, naphthalene type, and dioxane type. The non-polymerizable liquid crystal compound LCM is one type of liquid crystal compound or a combination of two or more types of liquid crystal compounds.
[0045] An example of the non-polymerizable liquid crystal compound LCM is represented by the following formula (10). R 11 -A 11 -Z 11 -A 12 -Z 12 -A 13 -Z 13 -A 14 -R 12 …(10) R 11 R is a hydrogen atom or an alkyl group having 1 to 20 carbon atoms. 11 One or two or more non-adjacent methylene bonds contained in the alkyl group can be substituted with any bond selected from the group consisting of an oxygen atom, an ethylene bond, an ester bond, and a diether bond.
[0046] R 12 R is a hydrogen atom, a fluorine atom, a chlorine atom, a cyano group, a trifluoromethyl group, a trifluoromethoxy group, a difluoromethoxy group, or an alkyl group having 1 to 15 carbon atoms.12 One or two or more non-adjacent methylene bonds contained in the alkyl group can be substituted with any bond selected from the group consisting of an oxygen atom, an ethylene bond, an ester bond, and a diether bond.
[0047] A 11 , A 12 , A 13 , A 14 each independently represents a 1,4-phenylene group or a 2,6-naphthylene group. One or more hydrogen atoms of the 1,4-phenylene group or the 2,6-naphthylene group can be substituted with a fluorine atom, a chlorine atom, a trifluoromethyl group, or a trifluoromethoxy group. 11 , A 12 , A 13 , A 14 may each independently be a 1,4-cyclohexylene group, a 3,6-cyclohexenylene group, a 1,3-dioxane-2,5-diyl group, or a pyridine-2,5-diyl group. 13 , A 14 may each independently be a single bond.
[0048] Z 11 , Z 12 , Z 13 each independently represents any one selected from the group consisting of a single bond, an ester bond, a diether bond, an ethylene bond, a fluoroethylene bond, and a carbonyl bond.
[0049] The speed at which the orientation state of the non-polymerizable liquid crystal compound LCM changes in response to a change in the potential difference changes non-linearly with respect to the environmental temperature, and the lower the environmental temperature, the slower the change. It is particularly difficult for the non-polymerizable liquid crystal compound LCM to change its long axis direction in the gap 31D partitioned by the organic polymer layer 31P, compared to a structure in which the liquid crystal composition 31LC is filled in a wide layered space, such as a liquid crystal panel used in a display device. The responsiveness of the non-polymerizable liquid crystal compound LCM depends greatly on the interaction between the molecules of the non-polymerizable liquid crystal compound LCM.
[0050] The NI point of a non-polymerizable liquid crystal compound LCM is the temperature at which the non-polymerizable liquid crystal compound LCM undergoes a phase transition from a nematic phase (N phase) to an isotropic liquid phase (I phase). The NI point of a non-polymerizable liquid crystal compound LCM indicates the degree to which the anisotropy of the non-polymerizable liquid crystal compound LCM disappears at ambient temperature. The NI point of a non-polymerizable liquid crystal compound LCM also reflects the degree of intermolecular interaction in the non-polymerizable liquid crystal compound LCM to a certain extent.
[0051] When the non-polymerizable liquid crystal compound LCM is a combination of two or more liquid crystal compounds, the NI point of the non-polymerizable liquid crystal compound LCM is a weighted average of the NI points of each liquid crystal compound, weighted by the blending ratio of each liquid crystal compound. The NI point of the non-polymerizable liquid crystal compound LCM can be increased or decreased by the composition of two or more liquid crystal compounds having different NI points.
[0052] When it is required to improve the orientation order of the non-polymerizable liquid crystal compound LCM at a high environmental temperature such as 100° C., the NI point is preferably high, and more preferably 100° C. or higher. When it is required to improve the homogenization of the non-polymerizable liquid crystal compound LCM and the photopolymerizable compound, the NI point is preferably low, and more preferably 145° C. or lower.
[0053] The CN point of a non-polymerizable liquid crystal compound LCM is the temperature at which the non-polymerizable liquid crystal compound LCM undergoes a phase transition from a crystalline phase (C phase) to a nematic phase (N phase). The CN point of a non-polymerizable liquid crystal compound LCM indicates the degree to which the fluidity of the non-polymerizable liquid crystal compound LCM is lost at ambient temperature. The CN point of a non-polymerizable liquid crystal compound LCM also largely reflects the degree of intermolecular interaction in the non-polymerizable liquid crystal compound LCM.
[0054] When the non-polymerizable liquid crystal compound LCM is a combination of two or more liquid crystal compounds, the CN point of the non-polymerizable liquid crystal compound LCM is a weighted average of the CN points of each liquid crystal compound, weighted by the blending ratio of each liquid crystal compound. The CN point of the non-polymerizable liquid crystal compound LCM can be increased or decreased by the composition of two or more liquid crystal compounds having different NI points.
[0055] When it is required to increase the fluidity of the non-polymerizable liquid crystal compound LCM at a high environmental temperature such as -20°C, the CN point is preferably low, more preferably 25°C or lower, and even more preferably 0°C or lower.
[0056] The refractive index difference Δn (Δn=extraordinary light refractive index ne-ordinary light refractive index no) between the long axis direction and the short axis direction of the non-polymerizable liquid crystal compound LCM indicates the degree of intermolecular interaction in the non-polymerizable liquid crystal compound LCM. The refractive index difference Δn of the non-polymerizable liquid crystal compound LCM is the difference in refractive index of visible light having a wavelength of 650 nm, and indicates the difference in the degree of scattering of visible light between when a driving voltage is applied and when it is not applied. When the non-polymerizable liquid crystal compound LCM is a combination of two or more liquid crystal compounds, the upper limit value of the refractive index difference Δn of the non-polymerizable liquid crystal compound LCM is the upper limit value obtained from the refractive index difference Δn of all the liquid crystal compounds. The lower limit value of the refractive index difference Δn of the non-polymerizable liquid crystal compound LCM is the lower limit value obtained from the refractive index difference Δn of all the liquid crystal compounds.
[0057] When it is necessary to increase the alignment controllability of the non-polymerizable liquid crystal compound LCM at a high environmental temperature, it is preferable that the lower limit value of the refractive index difference Δn is high. When it is necessary to increase the difference in haze between the transparent state and the opaque state, it is preferable that the lower limit value of the refractive index difference Δn is high. When it is necessary to increase the alignment controllability of the non-polymerizable liquid crystal compound LCM at a high environmental temperature such as 100° C., it is preferable that the lower limit value of the refractive index difference Δn of the non-polymerizable liquid crystal compound LCM is 0.005, and more preferably 0.01. Alternatively, when it is necessary to increase the difference in haze, it is preferable that the lower limit value of the refractive index difference Δn of the non-polymerizable liquid crystal compound LCM is 0.005, and more preferably 0.01.
[0058] When it is necessary to improve the responsiveness of the transmittance at a low environmental temperature, it is preferable that the upper limit of the refractive index difference Δn is low. When it is necessary to further improve the responsiveness of the transmittance at a low environmental temperature such as -20°C, the upper limit of the refractive index difference Δn of the non-polymerizable liquid crystal compound LCM is 0.028, more preferably 0.02.
[0059] [Non-polymerizable viscosity reducing agent] The non-polymerizable viscosity reducing agent DP contains a non-polar group such as an alkyl group for weakening the intermolecular interaction between adjacent non-polymerizable liquid crystal compounds LCM. The non-polymerizable viscosity reducing agent DP contains a polar group such as an ester bond having a polarity that interacts with the polarity of the non-polymerizable liquid crystal compound LCM.
[0060] The non-polymerizable viscosity reducing agent DP is represented by the following formula (1) or formula (3). An example of the non-polymerizable viscosity reducing agent DP represented by formula (1) is at least one selected from the group consisting of dibutyl adipate, bis(2-ethylhexyl) adipate, diisononyl adipate, diisodecyl adipate, bis(2-butoxyethyl) adipate, diethyl malonate, di-n-butyl phthalate, bis(2-ethylhexyl) phthalate, tris(2-ethylhexyl) trimellitate, tributyl o-acetylcitrate, and methyl benzoate. An example of the non-polymerizable viscosity reducing agent DP represented by formula (3) is at least one selected from the group consisting of tripropyl phosphate, tributyl phosphate, and tripentyl phosphate. The non-polymerizable viscosity reducing agent DP is one type of viscosity reducing agent or a combination of two or more types of viscosity reducing agents.
[0061] [ka] X in formula (1) is a linear or branched alkyl group having 1 to 6 carbon atoms, or an aryl group. 1 , R 2 , R 3 are each independently a hydrogen atom or a functional group represented by formula (2). 4 is a straight-chain or branched alkyl group or an ether group having from 1 to 10 carbon atoms.
[0062] [ka] r in formula (2) 5is a straight-chain or branched alkyl group or an ether group having from 1 to 10 carbon atoms.
[0063] [ka] r in Equation (3) 6 , r 7 , r 8 are each independently a linear alkyl group having 3 to 6 carbon atoms or an ether group.
[0064] The lower limit of the content of the non-polymerizable viscosity reducing agent DP relative to the total amount of the non-polymerizable liquid crystal compound LCM and the non-polymerizable viscosity reducing agent DP is 0.6% by mass, more preferably 1% by mass, and even more preferably 2% by mass. The upper limit of the content of the non-polymerizable viscosity reducing agent DP relative to the total amount of the non-polymerizable liquid crystal compound LCM and the non-polymerizable viscosity reducing agent DP is 10% by mass, more preferably 8% by mass, and even more preferably 6% by mass.
[0065] When it is required to improve the alignment controllability of the non-polymerizable liquid crystal compound LCM at a high environmental temperature, it is preferable that the upper limit of the content of the non-polymerizable viscosity reducer DP is low.When it is required to improve the responsiveness of the transmittance at a low environmental temperature, it is preferable that the upper limit of the content of the non-polymerizable liquid crystal compound LCM is high.
[0066] The dichroic dye is driven by a guest-host system using a non-polymerizable liquid crystal compound (LCM) as a host, and exhibits color. The dichroic dye is at least one selected from the group consisting of polyiodine, azo compounds, anthraquinone compounds, naphthoquinone compounds, azomethine compounds, tetrazine compounds, quinophthalone compounds, merocyanine compounds, perylene compounds, and dioxazine compounds. The dichroic dye is one type of compound or a combination of two or more types of compounds.
[0067] When it is required to increase the light fastness and the dichroic ratio, the dichroic dye is at least one selected from the group consisting of an azo compound and an anthraquinone compound, and more preferably an azo compound.
[0068] The spacers SP are dispersed throughout the organic polymer layer 31P. The spacers SP determine the thickness of the light-controlling layer 31 around the spacers SP and make the thickness of the light-controlling layer 31 uniform. The spacers SP may be bead spacers or photospacers formed by exposing and developing a photoresist. The spacers SP may be colorless and transparent or colored and transparent. When the liquid crystal composition 31LC contains a dichroic dye, it is preferable that the color exhibited by the spacers SP is the same color as the color exhibited by the dichroic dye.
[0069] The light-adjusting sheet 11 may have other functional layers as long as the light-adjusting sheet 11 is configured to switch between a transparent state and an opaque state based on a change in the alignment state of the non-polymerizable liquid crystal compound LCM caused by application of a voltage. The other functional layers may be a gas barrier layer that suppresses the transmission of oxygen and moisture toward the light-adjusting layer 31, or an ultraviolet barrier layer that suppresses the transmission of ultraviolet light rays other than a specific wavelength toward the light-adjusting layer 31. The other functional layers may be a hard coat layer that mechanically protects each layer of the light-adjusting sheet 11, or an adhesive layer that enhances adhesion between layers in the light-adjusting sheet 11.
[0070] [Manufacturing method of light control sheet] The manufacturing method of the light control sheet 11 includes forming a coating film containing the above-mentioned photopolymerizable compound and liquid crystal composition 31LC between the first transparent support layer 36 and the second transparent support layer 37. The first transparent support layer 36 includes a first alignment layer 32 and a first transparent electrode layer 34. The second transparent support layer 37 includes a second alignment layer 33 and a second transparent electrode layer 35. In the manufacturing method of the light control sheet 11 in which the first alignment layer 32 and the second alignment layer 33 are omitted, a coating film containing the above-mentioned photopolymerizable compound and liquid crystal composition 31LC is formed between the first transparent support layer 36 and the second transparent support layer 37. The first transparent support layer 36 includes the first transparent electrode layer 34, with the first alignment layer 32 omitted. The second transparent support layer 37 includes the second transparent electrode layer 35, with the second alignment layer 33 omitted.
[0071] The coating film contains a polymerization initiator for initiating polymerization of the photopolymerizable compound. The polymerization initiator is at least one selected from the group consisting of a diketone compound, an acetophenone compound, a benzoin compound, a benzophenone compound, and a thioxanthone compound. The polymerization initiator may be one type of compound or a combination of two or more types of compounds. An example of the polymerization initiator is any one selected from the group consisting of benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and cyclohexyl phenyl ketone.
[0072] The manufacturing method of the light controlling sheet 11 includes polymerizing a photopolymerizable compound in the coating film, thereby phase-separating liquid crystal particles made of the liquid crystal composition 31LC from the polymer. The light for polymerizing the photopolymerizable compound may be ultraviolet light or an electron beam. The light irradiated to the coating film may be irradiated toward the first transparent support layer 36, may be irradiated toward the second transparent support layer 37, or may be a combination of these.
[0073] Phase separation of liquid crystal particles made of liquid crystal composition 31LC proceeds through polymerization of the photopolymerizable compound and diffusion of liquid crystal composition 31LC. The polymerization speed of the photopolymerizable compound varies depending on the intensity of light irradiated to the photopolymerizable compound. The diffusion speed of liquid crystal composition 31LC varies depending on the processing temperature during polymerization of the photopolymerizable compound. In phase separation of liquid crystal composition 31LC, the intensity of light irradiated to the photopolymerizable compound is set so that the size of the liquid crystal particles is the desired size, that is, so that the size of void 31D is the desired size. In addition, in phase separation of liquid crystal composition 31LC, heating may be performed to promote diffusion of liquid crystal composition 31LC.
[0074] When it is required to reduce the size of the voids 31D, it is preferable to increase the intensity of the light irradiated to the photopolymerizable compound and proceed with the polymerization at a low temperature to suppress the diffusion of the liquid crystal composition 31LC.When it is required to increase the size of the voids 31D, it is preferable to decrease the intensity of the light irradiated to the photopolymerizable compound and proceed with the polymerization at a high temperature to promote the diffusion of the liquid crystal composition 31LC.
[0075] [Example] Specific examples and comparative examples of the light control sheet 11 are shown below. Each example and comparative example is a normal type light control sheet 11 in which the first alignment layer 32 and the second alignment layer 33 are omitted. Then, a coating film containing a photopolymerizable compound and a liquid crystal composition 31LC was formed between a first transparent support layer 36 having a first transparent electrode layer 34 and a second transparent support layer 37 having a second transparent electrode layer 35, and the light control sheet 11 was obtained by polymerizing the photopolymerizable compound in the coating film.
[0076] The constituent materials used in the examples and comparative examples are shown below. The NI point of the non-polymerizable liquid crystal compound LCM is 110°C. The compounding ratios of the constituent materials in Examples 1 to 41 and Comparative Examples 1 to 7 are shown in Figures 3 to 7. The compounding ratios shown in Figures 3 to 7 indicate the ratio of each constituent material to the total amount of the coating liquid for forming a coating film.
[0077] First transparent electrode layer 34: indium tin oxide Second transparent electrode layer 35: indium tin oxide · First transparent support layer 36: polyethylene terephthalate film · Second transparent support layer 37: Polyethylene terephthalate film Polymerization initiator PI1: 1-hydroxycyclohexyl phenyl ketone Non-polymerizable liquid crystal compounds LCM: Cyanobiphenyl compounds Spacer SP: Spherical with a diameter of 15 μm (PMMA) ·Ultraviolet polymerizable compounds (polymerizable unsaturated compounds) Component M1: Isobornyl acrylate Component M2: Pentaerythritol triacrylate Component M3: Urethane acrylate
[0078] ·Non-polymerizable viscosity reducer DP (non-polymerizable additive) Component NPA1: Dibutyl adipate Ingredient NPA2: Dioctyl adipate Component NPA3: Diisononyl adipate Component NPA4: Diisodecyl adipate Component NPA5: Bis(2-butoxyethyl) adipate Component NPA6: Diethyl malonate Component NPA7: Di-n-butyl phthalate Component NPA8: Bis(2-ethylhexyl) phthalate Ingredient NPA9: Tris(2-ethylhexyl) trimellitate Component NPA10: Tributyl o-acetyl citrate Ingredient NPA11: Methyl benzoate Component NPA12: Tributyl phosphate polymerizable additive Component MA1: Butyl acrylate Component MA2: Triethylene glycol diacrylate Component MA3: Pentaerythritol triacrylate
[0079] (Examples 1 to 6) As shown in FIG. 3, the coating liquids of Examples 1 to 6 each used 0.5 mass % of components NPA1 to NPA6 as the non-polymerizable viscosity reducer DP. Using the coating liquids of Examples 1 to 6, a coating film having a thickness of 20 μm was formed on the first transparent electrode layer 34, and spacers SP were sprayed into the coating film. The coating film on which the spacers SP were sprayed was then laminated with the first transparent electrode layer 34 and the second transparent electrode layer 35, and 365 nm ultraviolet light was irradiated toward the first transparent support layer 36 to obtain the light control sheets 11 of Examples 1 to 6. At this time, the intensity of the ultraviolet light was set to 10 mW / cm 2 and the UV irradiation time was set to 100 seconds.
[0080] (Examples 7 to 12) 3 and 4, the coating liquids of Examples 7 to 12 each contained 1.0 mass% of component NPA1 to component NPA6 as the non-polymerizable viscosity reducing agent DP. The light control sheets 11 of Examples 7 to 12 were obtained in the same manner as in Example 1 except for the blending ratio of the non-polymerizable viscosity reducing agent DP and the blending ratio of the ultraviolet-polymerizable compound.
[0081] (Examples 13 to 18) 4, the coating liquids of Examples 13 to 18 each contained 2.0 mass% of components NPA1 to NPA6 as the non-polymerizable viscosity reducing agent DP. The light control sheets 11 of Examples 13 to 18 were obtained in the same manner as in Example 1 except for the blending ratio of the non-polymerizable viscosity reducing agent DP and the blending ratio of the ultraviolet-polymerizable compound.
[0082] (Example 19 to Example 30) 4 and 5, the coating liquids of Examples 19 to 30 each contained 3.0 mass% of components NPA1 to NPA12 as the non-polymerizable viscosity reducing agent DP. The light control sheets 11 of Examples 19 to 30 were obtained in the same manner as in Example 1 except for the blending ratio of the non-polymerizable viscosity reducing agent DP and the blending ratio of the ultraviolet-polymerizable compound.
[0083] (Examples 31 to 36) 6, the coating liquids of Examples 31 to 36 each contained 4.0 mass% of component NPA1 to component NPA6 as the non-polymerizable viscosity reducing agent DP. The light control sheets 11 of Examples 31 to 36 were obtained in the same manner as in Example 1 except for the blending ratio of the non-polymerizable viscosity reducing agent DP and the blending ratio of the ultraviolet-polymerizable compound.
[0084] (Example 37 to Example 39) 6, the coating liquids of Examples 37 to 39 each contained 5.0 mass% of component NPA3, component NPA5, and component NPA6 as the non-polymerizable viscosity reducing agent DP. The light control sheets 11 of Examples 37 to 39 were obtained in the same manner as in Example 1 except for the blending ratio of the non-polymerizable viscosity reducing agent DP and the blending ratio of the ultraviolet-polymerizable compound.
[0085] (Example 40 to Example 41) 6, the coating liquids of Examples 40 to 41 each contained 0.3 mass% of component NPA4 and component NPA6 as the non-polymerizable viscosity reducing agent DP. The light control sheets 11 of Examples 40 to 41 were obtained in the same manner as in Example 1 except for the blending ratio of the non-polymerizable viscosity reducing agent DP and the blending ratio of the ultraviolet-polymerizable compound.
[0086] Comparative Example 1 As shown in Figure 7, a coating liquid was used in which the non-polymerizable viscosity reducing agent DP was omitted, and the light-control sheet 11 of Comparative Example 1 was obtained in the same manner as in Example 1 except for omitting the non-polymerizable viscosity reducing agent DP and the compounding ratio of the ultraviolet-polymerizable compound.
[0087] (Comparative Example 2 to Comparative Example 3) As shown in Figure 7, a coating liquid was used in which the non-polymerizable viscosity reducing agent DP was omitted and 0.5 mass% of component MA1 was added as a polymerizable additive, and the light-control sheet 11 of Comparative Example 2 was obtained in the same manner as in Example 1 except for omitting the non-polymerizable viscosity reducing agent DP, adding the polymerizable additive, and changing the compounding ratio of the ultraviolet-polymerizable compound.
[0088] In addition, a coating liquid was used in which the non-polymerizable viscosity reducing agent DP was omitted and 4.0 mass% of component MA1 was added as a polymerizable additive, and the light-controlling sheet 11 of Comparative Example 3 was obtained in the same manner as in Example 1 except for omitting the non-polymerizable viscosity reducing agent DP, adding the polymerizable additive, and the compounding ratio of the ultraviolet-polymerizable compound.
[0089] (Comparative Examples 4 to 5) As shown in Figure 7, a coating liquid was used in which the non-polymerizable viscosity reducing agent DP was omitted and 0.5 mass% of component MA2 was added as a polymerizable additive, and the light-control sheet 11 of Comparative Example 4 was obtained in the same manner as in Example 1 except for omitting the non-polymerizable viscosity reducing agent DP, adding the polymerizable additive, and changing the compounding ratio of the ultraviolet-polymerizable compound.
[0090] In addition, a coating liquid was used in which the non-polymerizable viscosity reducing agent DP was omitted and 4.0 mass% of component MA2 was added as a polymerizable additive, and the same procedures were followed as in Example 1 except for omitting the non-polymerizable viscosity reducing agent DP, adding the polymerizable additive, and the compounding ratio of the ultraviolet-polymerizable compound, to obtain a light-controlling sheet 11 of Comparative Example 5.
[0091] (Comparative Examples 6 to 7) As shown in Figure 7, a coating liquid was used in which the non-polymerizable viscosity reducing agent DP was omitted and 0.5 mass% of component MA3 was added as a polymerizable additive, and the light-control sheet 11 of Comparative Example 6 was obtained in the same manner as in Example 1 except for omitting the non-polymerizable viscosity reducing agent DP, adding the polymerizable additive, and changing the compounding ratio of the ultraviolet-polymerizable compound.
[0092] In addition, a coating liquid was used in which the non-polymerizable viscosity reducing agent DP was omitted and 4.0 mass% of component MA3 was added as a polymerizable additive, and the light-control sheet 11 of Comparative Example 7 was obtained in the same manner as in Example 1 except for omitting the non-polymerizable viscosity reducing agent DP, adding the polymerizable additive, and the compounding ratio of the ultraviolet-polymerizable compound.
[0093] [evaluation] Using the light-adjusting sheets 11 of Examples 1 to 41 and Comparative Examples 1 to 7, the haze of the light-adjusting sheets 11 in an opaque state (when no current is applied) and the haze of the light-adjusting sheets 11 in a transparent state (when current is applied) were measured at temperatures of -20°C, -10°C, 0°C, 23°C, 90°C, and 100°C, respectively.
[0094] Using the light controlling sheets 11 of Examples 1 to 41 and Comparative Examples 1 to 7, the time required for the light controlling sheet 11 to switch from an opaque state to a transparent state was measured as an on-operation at temperatures of -20° C., -10° C., and 23° C. The time required to switch from an opaque state to a transparent state is the time from when the application of the driving voltage begins until the haze of the light controlling sheet 11 becomes stable.
[0095] Using the light controlling sheets 11 of Examples 1 to 41 and Comparative Examples 1 to 7, the time required for the light controlling sheets 11 to switch from a transparent state to an opaque state was measured in off operation at temperatures of −20° C., −10° C., and 23° C. The time required to switch from a transparent state to an opaque state is the time required from when the application of the driving voltage is stopped until the haze of the light controlling sheet 11 becomes stable.
[0096] It was found that the ON operation at −20° C. in Examples 1 to 41 was 5 seconds or less in all cases, while the ON operation at −20° C. in Comparative Examples 1 to 7 was 7 seconds or more in all cases. This shows that the addition of components NPA1 to NPA12 as the non-polymerizable viscosity reducing agent DP can improve the responsiveness of the ON operation at −20° C. compared to the case where no non-polymerizable viscosity reducing agent DP is added or the case where a polymerizable additive is added.
[0097] Also, it was found that the difference between the ON operation at -20°C and the ON operation at 23°C was 4 seconds or less in all of Examples 1 to 41, while it was 6 seconds or more in all of Comparative Examples 1 to 7. This shows that the addition of components NPA1 to NPA12 as the non-polymerizable viscosity reducing agent DP can suppress the degree of decrease in the responsiveness of the ON operation caused by a decrease in temperature, compared to the case where the non-polymerizable viscosity reducing agent DP is not added or the case where a polymerizable additive is added.
[0098] Moreover, it was found that the haze in the transparent state of Examples 1 to 39 was 6% or less, while the haze in the transparent state of Examples 40 and 41 was 7% or more. This indicates that the haze in the transparent state can be suppressed if the ratio of the non-polymerizable viscosity reducing agent DP to the weight of the non-polymerizable liquid crystal compound LCM is 1% or more.
[0099] Comparing the haze in the transparent state of Examples 7 to 39 with the haze in the transparent state of Examples 1 to 6, it was found that the haze in the transparent state can be further suppressed when the ratio of the non-polymerizable viscosity reducing agent DP to the weight of the non-polymerizable liquid crystal compound LCM is 2% or more.
[0100] It was found that the haze in the opaque state of Examples 33, 35, and 36 was 85% or more at 100° C., while the haze in the opaque state of Examples 37, 38, and 39 was 83% or less at 100° C. This indicates that if the ratio of the non-polymerizable viscosity reducing agent DP to the weight of the non-polymerizable liquid crystal compound LCM is 8% or less, the decrease in haze in the opaque state can be suppressed.
[0101] Also, it was found that the difference between the haze in the opaque state at -20°C and the haze in the opaque state at 23°C was 10% or less in Examples 33, 35, and 36, while it was 12% or more in Examples 37, 38, and 39. This shows that if the ratio of the non-polymerizable viscosity reducing agent DP to the weight of the non-polymerizable liquid crystal compound LCM is 8% or less, the degree of decrease in the haze in the opaque state due to a decrease in temperature can be suppressed.
[0102] It was found that the haze in the transparent state at -20°C in Examples 19 to 23 was lower than that in the transparent state at -20°C in Examples 24, 27 to 30. It was also found that the haze in the opaque state at 100°C in Examples 19 to 23 was higher than that in the opaque state at 100°C in Examples 25 to 27. This shows that, when it is required to increase the alignment order of the non-polymerizable liquid crystal compound LCM at a low environmental temperature, it is preferable to use the components NPA1 to NPA6 among the non-polymerizable liquid crystal compounds LCM. Also, when it is required to increase the fluidity of the non-polymerizable liquid crystal compound LCM at a high environmental temperature, it is preferable to use the components NPA1 to NPA6 among the non-polymerizable liquid crystal compounds LCM.
[0103] According to the above embodiment, the following effects can be obtained. (1) If the liquid crystal composition 31LC contains the non-polymerizable viscosity reducing agent DP represented by the above formulas (1) to (3), the alkyl group, which is a non-polar group, is present between the non-polymerizable liquid crystal compounds LCM, weakening the intermolecular interaction in the non-polymerizable liquid crystal compounds LCM. This makes it possible to increase the response of the light transmittance at a low environmental temperature such as -20°C.
[0104] (2) The low molecular weight structures represented by the above formulas (1) to (3) are suitable for diffusing from the polymer of the ultraviolet-polymerizable compound, that is, for being phase-separated as liquid crystal particles from the organic polymer layer 31P.
[0105] (3) When the non-polymerizable viscosity reducing agent DP is an adipic acid ester, as in components NPA1 to NPA6, it is also possible to suppress a decrease in the orientational order of the non-polymerizable liquid crystal compound LCM at a low environmental temperature such as −20° C.
[0106] (4) When the ratio of the weight of the non-polymerizable viscosity reducing agent DP to the weight of the non-polymerizable liquid crystal compound LCM is 1% or more, it is possible to suppress the deterioration of the orientation order of the non-polymerizable liquid crystal compound LCM at a low environmental temperature such as -20°C.
[0107] (5) When the ratio of the weight of the non-polymerizable viscosity reducing agent DP to the weight of the non-polymerizable liquid crystal compound LCM is 2% or more and 8% or less, it becomes easy to control the transition of the non-polymerizable liquid crystal compound LCM to a disordered phase at a high environmental temperature such as 100°C. [Explanation of symbols]
[0108] DP: Non-polymerizable viscosity reducer LCM…Non-polymerizable liquid crystal compound SP…Spacer 11...Light-adjusting sheet 12...Drive unit 31...Photochromic layer 32...First alignment layer 33...Second alignment layer 34...First transparent electrode layer 35...Second transparent electrode layer 36...First transparent support layer 37…Second transparent support layer 31P…Organic polymer layer 31D…Void 31LC…Liquid crystal composition
Claims
1. an organic polymer layer defining a plurality of voids; a liquid crystal composition that contains a non-polymerizable liquid crystal compound and fills the gap; A light-controlling sheet that changes the transmittance of visible light by driving the non-polymerizable liquid crystal compound, a ratio of a weight of the organic polymer layer to a total weight of the organic polymer layer and the liquid crystal composition is 30% by mass or more and 60% by mass or less, the liquid crystal composition comprises a non-polymerizable viscosity reducing agent, All of the non-polymerizable viscosity reducing agents contained in the liquid crystal composition satisfy the following formula (1): The weight ratio of all the non-polymerizable viscosity reducing agents contained in the liquid crystal composition to the total weight of the non-polymerizable liquid crystal compound and the non-polymerizable viscosity reducing agent is 2% by mass or more and 6% by mass or less. 【Chemistry 1】 X is a linear or branched alkyl group having from 1 to 6 carbon atoms, or a group in which three hydrogen atoms bonded to one carbon or to each of different carbons constituting an aryl group have been removed; R 1 , R 2 , R 3 each independently represents a hydrogen atom or a functional group represented by formula (2) bonded to one carbon atom or each of the other carbon atoms constituting X; r 4 represents a linear or branched alkyl group or an ether group having from 1 to 10 carbon atoms; 【Chemistry 2】 r 5 is a linear or branched alkyl group or an ether group having 1 to 10 carbon atoms. Dimming sheet.
2. In the formula (1), X is a linear alkyl group having 1 to 6 carbon atoms. In the formula (1), R 1 is a functional group represented by the formula (2), In the formula (1), R 2 , R 3 are each independently a hydrogen atom The light controlling sheet according to claim 1 .
3. The non-polymerizable liquid crystal compound has an NI point of 100° C. or more and 145° C. or less. The light controlling sheet according to claim 1 or 2.
4. A method for producing a light control sheet, comprising: an organic polymer layer that defines a plurality of voids; and a liquid crystal composition that contains a non-polymerizable liquid crystal compound and fills the voids; and the light control sheet changes a transmittance of visible light by driving the non-polymerizable liquid crystal compound, and polymerizing the ultraviolet-curable compound in a layer containing the liquid crystal composition and the ultraviolet-curable compound to phase-separate liquid crystal particles made of the liquid crystal composition from the organic polymer layer, a ratio of a weight of the organic polymer layer to a total weight of the organic polymer layer and the liquid crystal composition is 30% by mass or more and 60% by mass or less, the liquid crystal composition comprises a non-polymerizable viscosity reducing agent, All of the non-polymerizable viscosity reducing agents contained in the liquid crystal composition satisfy the following formula (1): The weight ratio of all the non-polymerizable viscosity reducing agents contained in the liquid crystal composition to the total weight of the non-polymerizable liquid crystal compound and the non-polymerizable viscosity reducing agent is 2% by mass or more and 6% by mass or less. 【Chemistry 3】 X is a linear or branched alkyl group having from 1 to 6 carbon atoms, or a group in which three hydrogen atoms bonded to one carbon or to each of different carbons constituting an aryl group have been removed; R 1 , R 2 , R 3 each independently represents a hydrogen atom or a functional group represented by formula (2) bonded to one carbon atom or each of the other carbon atoms constituting X; r 4 represents a linear or branched alkyl group or an ether group having from 1 to 10 carbon atoms; 【Chemistry 4】 r 5 is a linear or branched alkyl group or an ether group having 1 to 10 carbon atoms. A method for manufacturing light-controlling sheets.
Citation Information
Patent Citations
Electro-optic material, optical element using that and phase space optical modulator
JP2000098358A
Light control film, light control device using the same, and screen
JP2018045135A
Liquid crystal compositions, mixtures, elements, and dimmable devices
WO2017180923A1